Revolución, federalismo y violencia ritual en el gobierno indígena de Peñas (1899) - Mendieta Parada, Pilar (Anuario de Historia de América Latina, 2021)
The following article deals with the political events taken place in Peñas (Oruro) during the so-called Federal War (1899) in Bolivia   between the political elites, the liberals from the northern region of La Paz, and the conservatives from the southern department of Chuquisaca for the political control of the country. The Aymara indigenous from the north, under the leadership of Pablo Zárate Willka, fought in defense of their ancestral territories. As a consequence, an indigenous government led by Juan Lero was established in Peñas. During that period, the indigenous tried to establish a form of federalism with aboriginal characteristics: a form of communal self-government under the concern of the to-be liberal Republic. At the same time, they executed a system of communal justice characterized by some forms of ritual violence. In this way, Peñas people used simultaneous and intertwined political and ritual strategies to legitimate their movement.
Keywords: Federal War; Pablo Zárate Willka; Juan Lero; Indigenous Government of Peñas